Continuous in-line decontamination of food-processing surfaces using cold atmospheric pressure air plasma. (October 2022) - Katsigiannis, Andreas S.; Hojnik, Nataša; Modic, Martina; Bayliss, Danny L.; Kovač, Janez; Walsh, James L.
Abstract: This study assessed a continuous in-line decontamination system for food contact surfaces and processing equipment that utilized cold atmospheric pressure plasma (CAP) generated from ambient air. The plasma system was evaluated against two common foodborne pathogens ( Salmonella Typhimurium, Listeria monocytogenes ) on stainless steel surfaces and against S Typhimurium on commercial poly[ether]-thermoplastic poly[urethane] (PE-TPU) conveyor belts, under simulated conditions of a food-processing facility. A significant level of microbial inactivation was achieved, up to 3.03 ± 0.18 and 2.77 ± 0.71 logCFU/mL reductions of L. monocytogenes and S . Typhimurium respectively within 10 s total treatment on stainless steel surfaces, and a 2.56 ± 0.37 logCFU/mL reduction of S. Typhimurium within 4 s total treatment on the PE-TPU material, according to a procedure based on the well-established EN 13697:2015 industrial protocol. CAP exposure was shown to have a minor impact on the morphology and composition of the treated surfaces. The results indicated that CAP can be applied for effective and continuous disinfection against common foodborne pathogens in food-processing facilities. Industrial relevance: Low temperature plasmas have shown great promise for microbial decontamination, yet industrial uptake of the technology has been limited due to scaling limitations. In this study, a prototype conveyor-based CAP decontamination system was developed and tested under realistic conditions expected within a food-processing facility. The results showed a high level of antimicrobial action against two common foodborne pathogens within a few seconds of CAP exposure, a timescale in line with industrial line processing speeds. Our findings demonstrated that CAP shows great promise for the continuous in-situ decontamination of food contact surfaces, with the potential to mitigate against the costly downtimes incurred in current production line practices implementing chemical disinfectants. Highlights: Cold plasma treatments were assessed on steel and polymer using simulated industry conditions. Up to 3.0 log CFU/mL bacteria were reduced in 10 s, and was affected by several processing factors. Minor oxidation and hydrophilicity changes affected long-term mechanical properties.